PERKEMBANGAN DAN DAMPAK FINANCIAL TECHNOLOGY (FINTECH) TERHADAP INDUSTRI KEUANGAN SYARIAH DI JAWA TENGAH - Miswan Ansori (Wahana Islamika: Jurnal Studi Keislaman, 2019)
Along with the development of the financial industry, technology is also growing with the emergence of Fintech (financial technology). Fintech is one of the innovations in the financial field that refers to modern technology. The growing existence of Fintech so that emerging Sharia-based Fintech and facilitating customers will certainly influence the formal Islamic finance industry such as Sharia Banks, Sharia BPRS, BMT and other formal Islamic finance industries where transactions in the formal sharia financial industry still use physical transactions in the transaction and have not made much use of the increasingly evolving technological advancements. This will make the formal financial industry less effective because of more costs and time spent. If the Islamic finance industry is unable to innovate and utilize technology, it will be far behind the Fintech-based financial industry whose development is very fast. This study was conducted to examine the development and impact of Fintech on the Islamic finance industry in Central Java. The research method used is a descriptive qualitative method and combines two types of research, namely field research and library research. Field research by collecting information from the Central Java Financial Services Authority (OJK), and from the Islamic Finance industry, namely BPRS Saka Dana Mulia Kudus.